Legal Protection Of Welfare Teacher Assistant Garden Children - Kusti'ah Kusti'ah (Law Development Journal, 2020)
The problems that arise in this research are: 1. What is the Realization of Legal Protection for Kindergarten Assistance Teachers' Welfare in Demak Regency, 2. What Barriers Arise in Protecting the Rights of Kindergarten Assistance Teachers in Demak Regency, 3 How is the Kindergarten Assistance Teacher Contract Completion after the employment contract ends.The method used in this research is qualitative descriptive with the research location in Demak Regency. Data sources use primary and secondary data. Respondents in this study were drawn by means of "purposive sampling". Data collection techniques by interview, observation and documentation. Data analysis uses inductive thinking with a flow analysis model which is divided into three main components. To determine the final result, an interactive analysis model is used.The results of the discussion and analysis of this study indicate that the Decree of the Minister of Education No. 034 / U / 2003 Regarding Assisted Teachers, it does not explicitly provide legal protection for the welfare of Kindergarten Assistance Teachers. Barriers that arise in protecting the rights of Assistance Teachers are the absence of the relevance of regulations applicable to Kindergarten Assistance Teachers. The completion of the Assistance Teacher contract agreement after the work contract ends, a Contract Agreement (SPK) is signed once a year until the age of 60 years, if evaluated it still meets the formal requirements. The implementation of legal protection for the welfare of Kindergarten Assistance Teachers has not been as expected.Keywords: Legal Protection, Assistance Teacher Welfare,